2018
DOI: 10.15171/mejdd.2017.85
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of NRAS Gene Mutation in Wild Type KRAS and BRAF Colorectal Cancers; a Single Center Study

Abstract: BACKGROUND Incidence of colorectal cancer is increasing in countries such as Iran. Molecular biomarkers play very important role in the diagnosis, treatment, and prognosis of this cancer. Mutation in the RAS family (including KRAS and NRAS) is one of these important molecular biomarkers, which should be tested before starting treatment with anti-EGRF (Epidermal growth factor) drugs. Objectives: There has been very few reports about the frequency of NRAS mutation from Iran and no study from south of the countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…The results of our study are in concordance with previous studies, where NRAS gene mutations were usually observed in codons 12 and 13 (exon 2), codon 61 (exon 3) and codons 117 and 146 (exon 4). Also, similarly to previous studies, where the frequency of these mutations ranged between 0 to 7.4 % (IRAHARA et al, 2010;AL-SHAMSI et al, 2016;MOMENZADEH et al, 2018;CHANG et al, 2016;BANDO et al, 2013;PALOMBA et al, 2016;NASERI et al, 2016;DOUILLARD et al, 2016), we have also noticed that frequency of NRAS gene mutation in patients with CRC is relatively low, i.e., of 55 tested patients in this study, only 3 of them (5.4%) had a mutation in NRAS gene. The results of the study of Prior and associates, 60% of NRAS mutations were found in codon 61 (PRIOR et al, 2012), and our study had similar results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of our study are in concordance with previous studies, where NRAS gene mutations were usually observed in codons 12 and 13 (exon 2), codon 61 (exon 3) and codons 117 and 146 (exon 4). Also, similarly to previous studies, where the frequency of these mutations ranged between 0 to 7.4 % (IRAHARA et al, 2010;AL-SHAMSI et al, 2016;MOMENZADEH et al, 2018;CHANG et al, 2016;BANDO et al, 2013;PALOMBA et al, 2016;NASERI et al, 2016;DOUILLARD et al, 2016), we have also noticed that frequency of NRAS gene mutation in patients with CRC is relatively low, i.e., of 55 tested patients in this study, only 3 of them (5.4%) had a mutation in NRAS gene. The results of the study of Prior and associates, 60% of NRAS mutations were found in codon 61 (PRIOR et al, 2012), and our study had similar results.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, many studies have shown that mutations in the NRAS gene can lead to low response on anti-EGFR therapy (IRAHARA et al, 2010;WANG et al, 2013;DI BARTOLOMEO et al, 2014;MODEST et al, 2016;AL-SHAMSI et al, 2016). That is why it is of crucial importance to additionally test CRC patients with wt KRAS for the presence of NRAS gene mutation (MOMENZADEH et al, 2018).…”
Section: Discussionmentioning
confidence: 99%